PPAR: a new pharmacological target for neuroprotection in stroke and neurodegenerative diseases. (25th October 2006) - Bordet, R.; Ouk, T.; Petrault, O.; Gelé, P.; Gautier, S.; Laprais, M.; Deplanque, D.; Duriez, P.; Staels, B.; Fruchart, J.C.; Bastide, M.
Abstract : PPARs (peroxisome-proliferator-activated receptors) are ligand-activated transcriptional factor receptors belonging to the so-called nuclear receptor family. The three isoforms of PPAR (α, β/δ and γ) are involved in regulation of lipid or glucose metabolism. Beyond metabolic effects, PPARα and PPARγ activation also induces anti-inflammatory and antioxidant effects in different organs. These pleiotropic effects explain why PPARα or PPARγ activation has been tested as a neuroprotective agent in cerebral ischaemia. Fibrates and other non-fibrate PPARα activators as well as thiazolidinediones and other non-thiazolidinedione PPARγ agonists have been demonstrated to induce both preventive and acute neuroprotection. This neuroprotective effect involves both cerebral and vascular mechanisms. PPAR activation induces a decrease in neuronal death by prevention of oxidative or inflammatory mechanisms implicated in cerebral injury. PPARα activation induces also a vascular protection as demonstrated by prevention of post-ischaemic endothelial dysfunction. These vascular effects result from a decrease in oxidative stress and prevention of adhesion proteins, such as vascular cell adhesion molecule 1 or intercellular cell-adhesion molecule 1. Moreover, PPAR activation might be able to induce neurorepair and endothelium regeneration. Beyond neuroprotection in cerebral ischaemia, PPARs are also pertinent pharmacological targets to induce neuroprotection in chronic neurodegenerative diseases.